Labor‐saving technologies and structural transformation in northern Ghana - Mueller, Valerie; Masias, Ian; Vallury, Sechindra (Wiley, 2019)
Labor‐saving technologies played a fundamental role historically in the structural transformation of agrarian economies. We focus on an emerging labor‐saving trend in Ghana, use of motorized tricycles (MTs), which provide an affordable alternative to manually transferring crops from plots to homestead. A household survey collected in 2017 in northern Ghana is used to shed light on how the time savings made available by using MTs may be converted into activities that enhance agricultural productivity and/or diversify the household away from agriculture. Detailed information collected on the agricultural production and agro‐processing behavior of 1,400 households allows us to examine the above transformative channels. Ordinary least squares and instrumental variable regressions are applied to quantify the effect of MTs on related outcomes. We find households are able to diversify their farming activities into selling processed agricultural goods with the time savings provided through MT adoption. Policies aimed to foster the diffusion of MTs elsewhere in Ghana may expedite structural change and, hence, economic growth.